Ferritin-Haemoglobin Ratio as a Predictor of Severity and Fatal Outcome in Patients with COVID-19 - Skakun, Oleksiy; Seredyuk, Nestor; Fedorov, Sergiy; Verbovska, Olha (Scripta Medica, 2023)
Background/Aim: Although ferritin and haemoglobin were well-studied for adverse outcome prediction in COVID-19 patients, a ferritin-haemoglobin ratio (FHR) was studied poorly. The study aimed to evaluate the prognostic ability of FHR at hospital admission in hypertensive and non-hypertensive patients with COVID-19.Methods: The study included 135 patients hospitalised for COVID-19-associated pneumonia. The 78.5 % of patients were hypertensive.Results: FHR at admission was higher in patients with critical condition (39.8 [17.1–83.0]) than in patients with moderate (22.0 [12.1–32.1], p = 0.01) and severe condition (34.6 [15.1–64.5], p = 0.01). FHR was higher in patients who required supplemental oxygen (40.4 [29.4–47.8]) than in patients without the need for supplemental oxygen (22.0 [18.0–25.5]) (p = 0.001). FHR at admission was higher in non-survivors (40.1 [24.6–95.9]) than in survivors (24.5 [21.6–28.4]) (p = 0.047). FHR showed weak discriminative ability for the prediction of severe/critical conditions in hypertensive patients (AUC = 0.636, p = 0.015) and all (hypertensive and non-hypertensive patients) patients (AUC = 0.658, p = 0.001), whereas FHR had an acceptable discriminative ability in non-hypertensive patients (AUC = 0.764, p = 0.015). There was an acceptable discriminative ability of FHR for in-hospital mortality prediction in hypertensive patients (AUC = 0.717, p = 0.029). Patients with FHR > 33.98 (Youden index, 0.39) had higher odds of severe/critical clinical condition (OR: 4.00; 95 % CI: 1.67–9.57; p = 0.02). FHR of > 37.64 (Youden index, 0.55) was associated with higher in-hospital mortality among hypertensive patients (OR: 11.42; 95 % CI: 2.31–56.47; p = 0.003). There was no difference in AUC for the discriminative ability of FHR regarding severe/critical condition (p = 0.296) and mortality (p = 0.663) in hypertensive and non-hypertensive patients.Conclusion: FHR at admission of > 33.98 is a predictor of severe/critical COVID-19 in both hypertensive and non-hypertensive patients. FHR of > 37.64 is a predictor of in-hospital mortality in hypertensive patients. There was no significant difference in the discriminative ability of FHR between hypertensive and non-hypertensive patients.
Keywords: COVID-19; Hypertension; Ferritin-haemoglobin ratio; Severity; Mortality